Respuesta :

Answer:

[tex]y=\frac{x^{2}-12}{11}[/tex].

Step-by-step explanation:

An inverse function is basically where you reflect the graph over the line x=y, , or when you switch the x and y points. Applying this logic, we have

[tex]x=\sqrt{11y+12},[/tex] where 11y+12 is greater than 0, so y is greater than -12/11. Squaring both sides in the first equation, we get [tex]x^{2}=11y+12[/tex] which is equal to [tex]y=\frac{x^{2}-12}{11}[/tex]. And that is your answer! Hope it helps!

Edit:

Don't forget that y is greater than [tex]-\frac{12}{11}[/tex]!

Answer:

The answer is [tex]f^(-1)(x)= (x^(2) - 12)/(11), x > =0[/tex]